Isolation of peptide ligands that interact specifically with human glioma cells - Ho, Ivy A.W.; Hui, Kam M.; Lam, Paula Y.P. (Peptides (New York, N.Y. : 1980), 2010)
Poor prognosis of high grade gliomas coupled with the difficulty of widespread delivery of therapeutic agents prompted the search into new molecular targets. Our aim is to isolate glioma-specific peptide sequences that can be used for targeted delivery of therapeutic drugs and imaging tracer to accurately demarcate tumor volume as a response to therapy. Herein, we describe the isolation and characterization of a glioma-specific peptide sequence, GL1, that interact exclusively with human glioma cells lines and primary glioma cells derived from human biopsy in vitro. Further analysis showed that the receptors for GL1 were located on the external side of the plasma membrane, where the GL1 peptides could bind stably up to a period of 180 min. More importantly, GL1 phages home specifically to human glioma xenograft when administered through tail vein, a phenomenon that was not observed when non-specific phages were used as control. Taken together, our results confirmed that GL1 could represent a novel peptide that target to tumor of glial origins, and could potentially be used as a targeting moiety for the conjugation of therapeutic drugs or diagnostic imaging radiolabels.